The city of your final destination a novel - Cameron, Peter 1959- (Farrar, Straus and Giroux, 2002)
Omar Razaghi travels to the estate of the late Uruguayan author Jules Gund in order to convince his three executors to let him write an authorized biography.
Keywords: Americans -- Uruguay -- Fiction; Biographers -- Fiction; Biography as a literary form -- Fiction; Graduate students -- Fiction; Humorous fiction.; Psychological fiction.; Kansas -- Fiction; Uruguay -- Fiction; Humorous fiction; Psychological fiction